Population dynamics and spatial distribution of the terrestrial snail Ovachlamys fulgens (Stylommatophora: Helicarionidae) in a tropical environment - Zaidett Barrientos (Revista de Biología Tropical, 2000)
The introduced snail Ovachlamys fulgens (Stylommatophora: Helicarionidae) occurs on cultivated land habitats in Costa Rica, where its macrodistribution seems to be limited by annual mean temperature (20 - 27.6°C) and annual precipitation (1 530 - 3 034 and 3 420 - 8 000 mm, with no more than six dry months). This species can be found in litter and on vegetation up to 70 cm tall. Random quadrat field sampling was done in leaf litter and understory plants every three months for a total of five dates in Central Costa Rica. At least 150 plots of 25x25 cm were analyzed on each date. Abundance of living specimens and eggs was positively correlated with (1) litter abundance and depth, (2) litter and soil humidity, (3) relative humidity and (4) early morning temperature (6:30 AM), and negatively correlated with temperature later in the morning (10:00 AM). Besides these factors, living snail abundance was correlated with thickness of the herbaceous vegetation and with the occurrence of Yucca elephantiphes (in litter and understory). Egg abundance was also correlated with the sampling date, apparently because of changes in humidity. The correlation pattern of shell abundance was opposite to that of living specimens. Population size and number of empty shells throughout the year parallel the rainfall pattern. Reproduction takes place between May and November (wet season); and up to 92% of the specimens can be found aestivating between December and April (dry season). Clutch size averages three eggs. The maximum density of living specimens was reached in December (43.41 ind/m²) and the minimum in March (8.30 ind/m²). Shells decompose in an average of five months. El caracol introducido Ovachlamys fulgens (Stylommatophora: Helicarionidae) habita regiones cultivadas de Costa Rica y su distribución está limitada por temperaturas anuales entre 20 y 27.6ºC y precipitaciones anuales entre 1530-3034 y 3420-8000 mm con no más de seis meses secos. Esta especie habita en la hojarasca y en la cobertura herbácea hasta a 70 cm de altura. Se realizaron cinco muestreos; uno cada tres meses. En cada muestreo se analizaron un mínimo de 150 parcelas aleatorias de 25 x25 cm. Los factores que determinan la abundancia de individuos y huevos fueron la abundancia y profundidad de la hojarasca, la humedad del mantillo y del suelo, y la humedad relativa. Éstos a su vez estuvieron positivamente correlacionados con la temperatura a primeras horas de la mañana (6:30 am) y negativamente con la temperatura a media mañana (10:00 am). Aparte de estos factores, los caracoles tambien estuvieron correlacionados con el grosor de la capa herbácea y con la presencia deYucca elephantipes tanto en el mantillo como en la vegetación. Los huevos tambien se vieron afectados por la época del año, debido a su propiedad higroscópica. La abundancia de conchas se correlacionó únicamente con la temperatura, en patrón contrario al de los los huevos. Tanto la población como la cantidad de conchas siguieron, con un leve retraso, la curva de lluvias de la zona a lo largo del año. La época reproductiva abarca los meses de mayo a noviembre (época lluviosa); y durante los meses de diciembre a abril (época seca) se puede encontrar hasta el 92% de los especímenes estivando. En condiciones naturales la camada promedio tiene tres huevos. Los caracoles vivos tuvieron una densidad máxima de 12.92 ind/m² (en diciembre) y mínima de 2.47 ind/m² (en marzo; estos valores deben multiplicarse por el factor de corrección 3.36). En condiciones experimentales las conchas tardaron intactas dos meses y su descomposición total se produjo en cinco meses en promedio.